Genomic and Phenotypic Analysis of an ESBL-Producing E. coli ST1159 Clonal Lineage From Wild Birds in Mongolia - Schierack, Peter; Heiden, Stefan E.; Khan, Muhammad Moman; Nikolaus, Lena; Kolenda, Rafal; Stubbe, Michael; Lkhagvasuren, Davaa; Rödiger, Stefan; Guenther, Sebastian; Schaufler, Katharina (Frontiers in Microbiology, 2020)
Background In addition to the broad dissemination of pathogenic extended-spectrum beta-lactamase (ESBL)-producing Escherichia (E.) coli in human and veterinary medicine and the community, their occurrence in wildlife and the environment is a growing concern. Wild birds in particular often carry clinically relevant ESBL-producing E. coli. Objectives We analyzed ESBL-producing and non-ESBL-producing E. coli obtained from wild birds in Mongolia to identify phylogenetic and functional characteristics that would explain the predominance of a particular E. coli clonal lineage in this area. Methods We investigated ESBL-producing E. coli using whole-genome sequencing and phylogenetics to describe the population structure, resistance and virulence features and performed phenotypic experiments like biofilm formation and adhesion to epithelial cells. We compared the phenotypic characteristics to non-ESBL-producing E. coli from the same background (Mongolian wild birds) and genomic results to publicly available genomes. Results & Conclusion We found ESBL-producing E. coli sequence type (ST) 1159 among wild birds in Mongolia. This clonal lineage carried virulence features typical for extra-intestinal pathogenic or enterotoxigenic E. coli. Comparative functional experiments suggested no burden of resistance in the ST1159 isolates, which is despite their carriage of ESBL-plasmids. Wild birds will likely disseminate these antibiotic-resistant pathogens further during migration.